The Long Arm and the Iron Fist: Authoritarian Crackdowns and Transnational Repression - Alexander Dukalskis; Saipira Furstenberg; Sebastian Hellmeier; Redmond Scales (Journal of Conflict Resolution, 2023)
The emerging literature dealing with transnational repression has identified several strategies used by authoritarian states to control and coerce their populations abroad. This article builds on existing research by investigating the domestic determinants of transnational repression. It argues that an increase in domestic repression is likely to lead to a subsequent increase in transnational repression because crackdowns at home drive dissent abroad and incentivize the state to extend its repressive gaze beyond its borders. To evaluate its arguments, the article draws on a database of approximately 1200 cases in which authoritarian states around the world threatened, attacked, extradited, abducted, or assassinated their own citizens abroad between 1991 and 2019. Offering a first quantitative test of domestic drivers of transnational repression, using multivariate regression analysis, the paper finds that as repression intensifies domestically, the likelihood of that state subsequently escalating its transnational repression also increases substantively.
https://doi.org/10.7910/DVN/WIXVLJ
Keywords: 320; repression; transnational repression; autocracy; dictatorship